Promoting Critical Thinking and Learning in a Large-Enrolment Humanities Class: A Case Study - Ragupathi, Kiruthika; Yeo, Zi Hui; Loy, Hui Chieh (Teaching and Learning Inquiry, 2022)
To promote the development of critical thinking abilities in an introductory undergraduate humanities course in the context of mass higher education, we implemented a course design that employed a series of scenario-based multiple-choice questions (MCQs) and informal peer discussions. Using an online survey to gather perception data and self-reported behavioral data, this study examines the extent to which the course design was effective at promoting critical thinking and student experience. Deductive analysis of students’ qualitative responses indicate that the course design was successful in promoting students’ development of critical thinking. Both deductive and inductive analysis of students’ qualitative responses also suggest that students largely had favorable attitudes towards this course design, though there are also some who express concerns. Our design may be useful for instructors and instructional designers aiming to promote critical thinking and learning in university courses.